2019
DOI: 10.1016/j.juro.2018.09.030
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Program to Reduce the Clinical Incidence of Clostridium difficile Colitis Infection after Cystectomy

Abstract: Clostridium difficile screening prior to cystectomy is associated with a significant decrease in rates of clinically symptomatic infections postoperatively. These results should be confirmed in a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Therefore, pre-operative screening can provide appropriate preventive measures. A study at Indiana University revealed that, for patients who tested positive for Clostridium difficile pre-surgery, immediate treatment with protective isolation and metronidazole reduced the rate of symptomatic infection post-surgery by about half ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pre-operative screening can provide appropriate preventive measures. A study at Indiana University revealed that, for patients who tested positive for Clostridium difficile pre-surgery, immediate treatment with protective isolation and metronidazole reduced the rate of symptomatic infection post-surgery by about half ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a provocative study Calaway et al (page 342) from Indianapolis, Indiana performed prospective screening for CD before surgery, and used contact isolation and prophylactic metronidazole in those who screened positive. 9 The incidence of clinical CD infection declined from 9.4% to 5.5%. Further studies are needed to learn whether CD prophylactic screening and treatment should be incorporated into enhanced recovery after surgery protocols.…”
Section: Screening Program To Reduce Clostridium Difficile Colitis Infection After Cystectomymentioning
confidence: 97%